Regional frequency analysis of extreme precipitation in Peninsular Malaysia / Iszuanie Syafidza Che Ilias ... [et al.] - Che Ilias, Iszuanie Syafidza; Wan Zin, Wan Zawiah; Jemain, Abdul Aziz (2021)
Peninsular Malaysia's climate is directly affected by wind from the mainland, being hot and humid throughout the year, it is categorized as equatorial due to its location near to the equator. This study employed the cluster analysis and regional frequency analysis based on L-moments to investigate the areas represented by data obtained from 32 measuring stations and TRMM. The study of the region, which is homogeneous in terms of L-moment ratios, defined the definition of homogeneous regions and identified the regional distribution and the identification of the best distribution based on LMoment Ratio Diagram (LMRD) and goodness-of-fit criterion. The results show that, for observation data, GLO was the most appropriate probability distribution for Region I, GNO for Region II, GEV for Region III, and GPA for Region IV. Meanwhile, for satellite data, the distribution functions were GPA for Region I, GEV for Region II, GLO for Region III, and the selected distribution for Region IV was GEV. The regional estimation based on Monte Carlo simulation, producing reliable rainfall quantiles were performed and the estimation of the quantiles, GNO, GEV, and GPA distributions gave approximately similar quantile estimates until 50 years return period. Results suggested that the estimation of extreme precipitation at ungauged sites with no flow data has become a real problem for scientists and hydrologists.